Estudio de la candidiasis oral en pacientes adultos sometidos a radioterapia que acuden a Solca-Loja en el periodo septiembre-diciembre 2022 - Carrillo Sisalima, Mirian Estefanía (2023)
Oral candidiasis is one of the most common opportunistic infections affecting the oral mucosa and arises due to the increase of Candida albicans species yeasts in both systemic and local conditions, being xerostomia and non-disinfected dental prostheses the predisposing local factors. This condition can cause worsening of the clinical condition in patients receiving radiotherapy treatments; therefore, it is recommended to treat it before, during and after treatment. The purpose of this research was to determine the prevalence of oral candidiasis in oncology patients undergoing radiotherapy who attended the Solca Cancer Institute Hospital in the city of Loja, as well as to study the influence of radiotherapy with the appearance of oral candidiasis, the incidence of radiation cycles between the appearance of oral candidiasis and the appearance of the pathology according to the irradiated site, through an analytical, cross-sectional study of cases and controls that was carried out with 26 patients as universe and 9 of them as sample. The dental history prepared specifically for the care of the patients of Solca Nucleo Loja was used, and the statistical analysis was carried out with the SPSS statistical package, using Pearson's Chi-square test. The results obtained were that 22.2% of the population studied presented oral candidiasis, while 77.8% did not present the pathology, however, there is no significant difference between the irradiated site and the presence of oral candidiasis, and an association between the radiation dose of 66 Gy with the appearance of oral candidiasis is suggested